Genome sequence of Microvirga lupini strain LUT6(T), a novel Lupinus alphaproteobacterial microsymbiont from Texas - Reeve, Wayne (Michigan State University, 2014)
Microvirga lupini LUT6(T) is an aerobic, non-motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as a legume microsymbiont of Lupinus texensis. LUT6(T) was isolated in 2006 from a nodule recovered from the roots of the annual L. texensis growing in Travis Co., Texas. LUT6(T) forms a highly specific nitrogen-fixing symbiosis with endemic L. texensis and no other Lupinus species can form an effective nitrogen-fixing symbiosis with this isolate. Here we describe the features of M. lupini LUT6(T), together with genome sequence information and its annotation. The 9,633,614 bp improved high quality draft genome is arranged into 160 scaffolds of 1,366 contigs containing 10,864 protein-coding genes and 87 RNA-only encoding genes, and is one of 20 rhizobial genomes sequenced as part of a DOE Joint Genome Institute 2010 Community Sequencing Project.